Wypracowanie uczniowskie jako dokument recepcji dzieła literackiego = Schoolboys' Compositions as Documents of Adoption of Literary Work - Świątyńska, Zofia (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article shows that a written composition with its liberal expression is a parrticulary diagnostic method in empirical researches on the recognition of the way of communing of pupils with a literary work.
Keywords: literatura polska - nauczanie; szkolnictwo